2018
DOI: 10.3390/met9010008
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Investigation of Recovery, Recrystallization and Austenite Transformation during Annealing of a Cold-Rolled Steel Using High Energy X-ray Diffraction (HEXRD)

Abstract: The annealing process of cold-rolled ferrite/pearlite steel involves numerous metallurgical mechanisms as recovery/recrystallization of deformed phases, ripening of carbide microstructure, and austenite transformation in the intercritical domain. The interactions between these mechanisms govern the morphogenesis of the transformed austenite microstructure and, thus, the final properties of the steel. This paper demonstrates that high energy X-ray diffraction (HEXRD) on synchrotron beamline offers the unique po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The density of dislocation in the deformed state has been estimated to be 1.7 × 10 15 m.m −3 . In the last part of this paper, the model will also be applied to the steel studied by Moreno et al (steel C) [7,23]. The purpose is to demonstrate that it is able to capture the effect of cold-reduction ratio on recrystallization kinetics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The density of dislocation in the deformed state has been estimated to be 1.7 × 10 15 m.m −3 . In the last part of this paper, the model will also be applied to the steel studied by Moreno et al (steel C) [7,23]. The purpose is to demonstrate that it is able to capture the effect of cold-reduction ratio on recrystallization kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…Different equations are proposed in the literature to model the evolution of the dislocation density as a function of time t and temperature T [25]. The model developed by Verdier et al [26] for Al-Mg alloys was able to reproduce some observed trends in ferritic steels but not it did not lead to a perfect agreement with the experimental data (e.g., data of Moreno et al [23]). For this reason, we could not justify the use of the complex model of Verdier et al and reverted to the original relaxation model of Friedel et al [27]:…”
Section: Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…A new method has been introduced recently to track in situ by HEXRD the recrystallization kinetics, together with the phase transformation kinetics [55]. This method is related to the presence of individual spots of intensity inside the Debye-Scherrer diffraction rings, which are ascribed to the new recrystallizing ferrite grains.…”
Section: High Energy X-ray Diffractionmentioning
confidence: 99%
“…A steel with composition Fe-0.1C-1.9Mn-0.2Cr-0.2Si wt.% with cold-rolled ferrite-pearlite initial microstructure is considered. A new experimental approach [55] is utilized to establish in situ by synchrotron high energy XRD the austenite transformation and the ferrite recovery/recrystallization global kinetics, in one single experiment. Three heating rates before isothermal annealing at 800°C are applied, fast (30 and 100°C.s -1 ) and slow (3°C.s -1 ) to induce strong or weak interactions.…”
Section: Introductionmentioning
confidence: 99%